Implementasi Metode SQ3R terhadap Keterampilan Literasi Membaca Siswa dalam Pembelajaran Teks Cerpen dengan Pendekatan Bimbingan dan Konseling Pendidikan Islam - Saiful Muktiali; Rini Setyowati; Nenda Nenda; Yossi Srianita; Unaisah Sunarsono (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
This study aimed to analyze the effectiveness of the SQ3R (Survey, Question, Read, Recite, Review) method integrated with the Islamic Educational Guidance and Counseling approach in improving students’ reading literacy skills in short story text learning. The study employed a quantitative approach using a quasi-experimental method with a pretest-posttest control group design. The research subjects consisted of two groups, namely the experimental group and the control group at SMKs Garuda Nusantara. Data collection techniques included reading comprehension tests, observation, interviews, and documentation. Data analysis was conducted through prerequisite tests, Wilcoxon Signed Rank Test, Mann-Whitney U Test, and N-Gain analysis. The results showed that the average pretest score of the experimental group was 69.05 and increased to 88.02 in the posttest, while the control group increased from 68.58 to 76.34. The Wilcoxon test result in the experimental group showed a significance value of 0.000 < 0.05, indicating a significant improvement in students’ reading comprehension skills after treatment. The Mann-Whitney test also showed a significance value of 0.001 < 0.05, indicating a significant difference between the experimental and control groups. Furthermore, the N-Gain score of the experimental group was 0.61 (moderate category), while the control group obtained 0.25 (low category). The findings indicate that the implementation of the SQ3R method integrated with the Islamic Educational Guidance and Counseling approach is effective in improving students’ reading literacy skills in short story learning.